Ti4+ Substitution on Structure and Conductivity of LiNi0.8Mn0.1Co(0.1-x)TixO2 as Battery Cathode (x = 0.01, 0.02, and 0.03) - Maya Puspitasari Izaak; Yohanes Edi Gunanto; Henni Sitompul; Yustinus Purwamargapratala (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2022)
Various cathodes have been studied to obtain cathode materials with high energy density and are inexpensive and environmentally friendly. Ti4+ substitution is one strategy to achieve this. Ti4+ doping has been done on Co2+ to reduce the level of toxicity. The objective of this research was to look at the impact of Ti4+ substitution on LiNi0.8Mn0.1Co(0.1-x)TixO2 so that it can be used as a battery cathode. The samples were prepared by the solid-state reaction method using high energy milling (HEM) in a wet state using ethanol. The phase formation of the material was characterized using XRD, surface morphology was characterized using SEM, and electrical conductivity was characterized using LCR-Meter. The finding showed that the particles experienced agglomeration, with the average size of the primary particles ranging from 300-500 nm and the secondary particle sizes ranging from 1-3mm. The morphology of the sample shows polycrystals. The maximum electronic conductivity obtained was 2.3 x 10-5, 2.4 x 10-5, and 3.2 x 10-5 S/cm for x = 0.01, 0.02, and 0.03, respectively. Another impact is increasing the cell volume and conductivity. With this high electrical conductivity value, this material is suitable for use as a battery cathode.